THE BUDGETING PROCESS IN THE NATIONAL AMIL ZAKAT AGENCY OF NURUL HAYAT - Dimas Mulya Pratama; Noven Suprayogi (Universitas Airlangga, 2020)
This research aims to find out the budgeting process of the National Amil Zakat Agency (LAZNAS) Nurul Hayat. The research data was obtained through the Nurul Hayat Foundation. The method used is a qualitative approach with a descriptive case study method. Data collection techniques using direct interviews. Interviews were conducted with the Director of Finance, Director of Operations, Director of Empowerment, and Director of ZIS. The analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that LAZNAS Nurul Hayat is an institution that uses a mixed method; the budgeting process includes the stages of preparation, budget ratification, implementation, and evaluation reporting. The budget system used is in accordance with a non-profit legal entity in the form of a foundation as stipulated in Law Number 28 of 2004.Keywords: budgeting process, non-profit, Nurul HayatREFFERENCE Kementerian Agama RI. (2017). Al-Qur’an dan terjemahnya. Jakarta: Adhi Aksara Abadi Indonesia.Anthony dan Govindarajan. (2005). Manajement control system, edisi 11, buku 2. Jakarta: Salemba Empat.Harahap, Don R. & M.M. Mowen. (2009). Akuntansi manajerial, edisi 8. Jakarta: Salemba Empat.Mardiasmo. (2002). Akuntansi sektor publik. Yogyakarta: Andi.Miles, B. Matew dan Michael Huberman. (1992). Analisis data kualitatif (buku sumber tentang metode-meode baru). Jakarta: UIPMunandar, M. (2001). Budgetting perencanaan kerja pengkoordinasian kerja pengawasan kerja. Yogyakarta: BPFEE-Yogyakarta.Mahsun, M. (2009). Pengukuran kinerja sektor publik. Yogyakarta: BPFE Yogyakarta.Nainggolan, Pahala. (2012). Manajemen keuangan lembaga nirlaba. Jakarta: Yayasan Bina Integrasi Edusi (YBIE).Nugraha, Adi. (2013). Analisis proses penyusunan rencana kerja dan anggaran Tahun 2013. Depok: Fakultas Ekonomi UI.Pandu, Tri M. P. (2013). Studi kasus proses penyusunan anggaran Badan Amil Zakat Nasional (BAZNAS). Depok: Fakultas Ekonomi UI.UU No 23 Tahun 2011 tentang Pengelolaan Zakat.Welsch, Glenn A. (1964). Budgeting profit planing and control, fourth edition. New Delhi: Prentice Hall of India Private Limited.Yin, Ribert K. (2012). Studi Kasus: Desain dan Metode. Jakarta: PT. Raja Grafindo Persada.